Social Media and Employee Productivity at Workplace - Celebi, Serra Inci; Terkan, Remziye (International Review of Management and Marketing, 2020)
This study makes theoretical contributions related to social media usage in the workplace. Participants who showed high work performance used social media to help communicate with their colleagues. People showed high work performance were also the ones escaping from an unsatisfying job for a while and escaping from a demanding job for a while by using social media in the workplace. High frequency of using social media in the workplace resulted in increased work performance. Keywords: Social media, work performance, and uses and gratifications. JEL Classifications: D83, L25 DOI: https://doi.org/10.32479/irmm.10806